Партызанская тэма ў аповесці Пушчанская адысея Аляксея Карпюка - Sakowicz, Anna (Acta Polono-Ruthenica, 2018)
The article is dedicated to the analysis of Alaksiej Karpiuk’s novel Puszczanskaja adysieja the theme of which is the guerrilla movement at the Byelorussian-Polish borderland. The novel’s main character Alosza Kuczyński struggles with the problems of incredulity, the lack of trust between people, antagonisms of national nature, destroying an orderly farmer’s world, the question about the value and the price of human life.